KLASIFIKASI FAKTOR PENYEBAB PERCERAIAN MENGGUNAKAN ALGORITMA C4.5 - Silitonga, Agnes Irene; Darwita Arini Nasution; Histi Trifesi Naibaho; Selvia Apriani; Dewi Pika Lumban Bantu (Universitas Methodist Indonesia, 2025)
Divorce is a complex social phenomenon that has significant impacts on individuals and society. In Indonesia, divorce is a serious concern for the government and society because the divorce rate has continued to increase in recent decades. Understanding the factors that contribute to divorce is essential to developing effective prevention strategies. The objective of this study is to classify the factors of divorce in Indonesia using the C4.5 algorithm, an algorithm used for data mining in building decision trees. This study used divorce data from 20 provinces in Indonesia in 2023 with various factors causing divorce. Divorce data was obtained from the Central Statistics Agency of Indonesia. The research process includes data collection, data pre-processing, and application of the C4.5 algorithm to build a classification model. The results of the study showed that continuous disputes and quarrels, apostasy, and economy are the most significant factors in divorce. The research results are expected to be a reference for policy makers and marriage counselors in formulating appropriate interventions to reduce divorce rates. The findings of this study can also serve as a foundation for establishing more effective policies and interventions to reduce divorce rates and enhance family institutions in Indonesia.